2007
DOI: 10.2136/sssaj2006.0400
|View full text |Cite
|
Sign up to set email alerts
|

Tillage Management Alters Surface Soil Organic Matter Composition: A Pyrolysis Mass Spectroscopy Study

Abstract: We examined the effects of 10 yr of reduced tillage (RT) management, compared with conventional tillage (CT), on the chemical composition of soil organic matter (SOM) using a combination of physical fractionation and pyrolysis–field ionization mass spectroscopy (Py–FIMS). Surface soil samples (0–10 cm), which were collected from two adjacent CT and RT managed fields, were separated into particulate organic matter (POM) fractions and sand, silt, and clay size separates. Higher amounts of C (77%) and N (64%) wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
20
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 40 publications
3
20
0
Order By: Relevance
“…2.2 1.6 3.6 1.6 1.6 1.8 2.3 2.1 (Düring et al, 2002) and, hence, its reactivity, are also affected by tillage (Ding et al, 2002a;Sleutel et al, 2007;Tatzber et al, 2008) and by the nature of crop residues (Ding et al, 2006). In soil organic matter collected under a no-tillage system, Preston et al (1994) found a higher number of reactive functional groups compared with that collected under a conventional tillage system.…”
Section: Organic Carbon Content Effectmentioning
confidence: 99%
“…2.2 1.6 3.6 1.6 1.6 1.8 2.3 2.1 (Düring et al, 2002) and, hence, its reactivity, are also affected by tillage (Ding et al, 2002a;Sleutel et al, 2007;Tatzber et al, 2008) and by the nature of crop residues (Ding et al, 2006). In soil organic matter collected under a no-tillage system, Preston et al (1994) found a higher number of reactive functional groups compared with that collected under a conventional tillage system.…”
Section: Organic Carbon Content Effectmentioning
confidence: 99%
“…After this soft ultrasonication, the > 53 lm fraction was removed by wet sieving, and a second ultrasonication at 440 J mL -1 was used to disperse the siltand clay-sized fraction. The probe energy supply was calibrated from the heating of water inside a dewar vessel (Sleutel et al, 2007b). The resulting soil suspension was separated into the clay-and silt-particle-size fractions by gravity sedimentation in water following Stoke's law.…”
Section: Characterization Of the Soil Mineral Matrix And Particle-sizmentioning
confidence: 99%
“…After soft ultrasonication at 60 J ml -1 , the [63 lm fraction was removed by wet sieving, and a second ultrasonication at 440 J ml -1 was used to disperse the silt and clay sized fraction. The probe energy supply was calibrated from the heating of water inside a dewar vessel (Sleutel et al 2007). Biogeochemistry (2008) 89:253-271 255 Chemical fractionation of SOM In search for a chemical fractionation procedure to isolate a stable SOM pool for process studies of SOM stabilization, Siregar et al (2005) concluded that threefold sequential 6 h 6% NaOCl treatments at pH 8 was most suitable for selective removal of OM, whilst minimally affecting the mineral soil constituents and hence mineral-associated OM.…”
Section: Study Area Description and Samplingmentioning
confidence: 99%